Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1996)
For this quarter's digest Professor Christian Herfarth and Dr Thomas Lehnert have selected the best from the October to December 1995 issues of Der Chirurg. A digest of the BJS for the same period, written by Mr Colin Johnson, appears in the German journal.